CX3CR1‐Expressing Myeloid Cells Regulate Host–Helminth Interaction and Lung Inflammation. Issue 3 (4th February 2022) - Kim, Sang Yong; Barnes, Mark A.; Sureshchandra, Suhas; Menicucci, Andrea R.; Patel, Jay J.; Messaoudi, Ilhem; Nair, Meera G.
Abstract: Many helminth life cycles, including hookworm, involve a mandatory lung phase, where myeloid and granulocyte subsets interact with the helminth and respond to infection‐induced lung injury. To evaluate these innate subsets in Nippostrongylus brasiliensis infection, reporter mice for myeloid cells (CX3CR1 GFP ) and granulocytes (PGRP dsRED ) are employed. Nippostrongylus infection induces lung infiltration of reporter cells, including CX3CR1 + myeloid cells and PGRP + eosinophils. Strikingly, CX3CR1 GFP/GFP mice, which are deficient in CX3CR1, are protected from Nippostrongylus infection with reduced weight loss, lung leukocyte infiltration, and worm burden compared to CX3CR1 +/+ mice. This protective effect is specific for CX3CR1 as CCR2‐deficient mice do not exhibit reduced worm burdens. Nippostrongylus co‐culture with lung Ly6C + monocytes or CD11c + cells demonstrates that CX3CR1 GFP/GFP monocytes secrete more pro‐inflammatory cytokines and actively bind the parasites causing reduced motility. RNA sequencing of Ly6C + or CD11c + cells shows Nippostrongylus ‐induced gene expression changes, particularly in monocytes, associated with inflammation, chemotaxis, and extracellular matrix remodeling pathways. Analysis reveals cytotoxic and adhesion molecules as potential effectors against the parasite, such as Gzma and Gzmb, which are elevated in CX3CR1 GFP/GFP monocytes. These studies validate a dual innate cell reporter for lung helminth infection and demonstrate that CX3CR1 impairs monocyte–helminth interaction. Abstract : Reporter transgenic mice are utilized to track CX3CR1‐GFP myeloid and PGRP‐dsRed granulocyte subsets following infection with lung helminth Nippostrongylus brasiliensis . CX3CR1‐deficient mice are further investigated, and a previously unrecognized role for CX3CR1 signaling in promoting infection‐induced pathology and impairing monocyte‐helminth interaction is identified. The RNA‐sequencing analysis identifies candidate cytotoxic molecules in lung monocytes that may contribute to effector responses against the helminth.